Place attachment process and its influence on neighborhood park utilization in Putrajaya, Malaysia - Amine, Moulay (2018)
Developing cities in the world are facing the challenging effect of rapid urbanization on their livability. Therefore, creating livable neighborhood has become a new urban agenda for the coming decades. Public spaces, including neighborhood parks, play a significant function in supporting the social life of a community since they are considered the backbone of the urban park systems. Nonetheless, many of the parks are underutilized. In the past, this issue was mainly considered in terms of physical and social attributes. However, less attention was directed to the psychological attachment process of park users, despite its crucial role in affecting their cognitions and behaviors. Furthermore, most studies on place attachment emphasize on the individual feeling and experiences, and have not placed these ties in the wider, socio-spatial context in which planners and urban designers operate. This is due to the multi-faceted, multi-disciplinary, multi-dimensional, and multi-paradigmatic nature of research on place attachment. The objective of this study is to explore the influence of the process of place attachment on neighborhood park utilization, reflected in the way individuals and groups relate to a place. This qualitative research inquiry purposively sampled twenty-nine park users living permanently and at least one year in the neighborhood of Precinct 9, in Putrajaya, the federal government administrative center for Malaysia. Through hermeneutic phenomenology, the informants were engaged to reflect their experiences of the park that matter most through probing questions. Data were collected through in-depth semi-structured interviews as the main method and supported by field observation method, then analyzed through Interpretative Phenomenological Analysis approach. This approach allowed the researcher to focus on the rich parts of the data and get initial themes from the transcript of each informant as an individual case. The second step was to refine the initial themes by turning conceptual connections into abstraction then coming out with more meaningful themes. The refined themes were cross-checked with the individual transcripts to note further information and deepen analysis, which allowed developing a master list of more concise themes. The last step was the development of an explanatory model supported by different narrative explanations. The findings revealed that the process of park‘s attachment covering the functional attachment, park‘s meaning and the emotional attachment, is interrelated. In the context of underutilized parks, the functional attachment was found to be the key concept that helps to attract residents to a neighborhood park. It is also intimately related to residents‘ contextual and functional needs, expressed mainly through physical activities in the park. In turn, the functional needs were embedded in the residents‘ motivation to stay healthy. Upon intensely linking all themes on the reason behind the process of park‘s attachment, the functional, emotional and natural motivations emerged. Residents‘ motivation to use the park is the larger frame under which the process of place attachment should be developed. It can be concluded that the quality of facilities for physical activities is the most vital factor in enhancing residents‘ attachment to the neighborhood park, leading to frequent park use. Furthermore, enhancing the process of park‘s attachment will support stronger place engagement and place dependency that could turn underutilized parks into responsive social places. The research findings provide a holistic view on the process of park‘s attachment to understand how the park‘s design may first enhance residents‘ engagement with their park, and second how the full potential of park use can be reached. The central message of this study is that integrating the psychological aspect of place attachment in the place-making process will help transform values of places into a responsive social environment.